Peran Stakeholder Dalam Mengatasi Perkawinan Anak Di Bawah Umur - Azizi, Alfian Qodri; Rofiq, M Khoirur (Indonesia, 2024)
Child marriage prevention is a shared responsibility carried out by various parties, which are then called stakeholders. Even so, child marriage still occurs a lot and continues to increase, one of which is in Kajoran District, Magelang. This study focuses on examining the factors of child marriage, the role of stakeholders, and obstacles to preventing child marriage in Kajoran District, Magelang. This study is qualitative and field research with a legal and sociological approach. Data sources from parents, stakeholders, and children. Data analysis includes data reduction, data display, and conclusions. The results of this study are: first, the factors of child marriage in Kajoran District are caused by the culture and mindset of the community that is permissive towards child marriage, low awareness of education, pregnancy outside of marriage, or intimate relationships outside of marriage. Second, the role of stakeholders in overcoming child marriage has been carried out according to regulations and their respective responsibilities but has not been optimal and synergistic. Third, the constraints of stakeholders in overcoming child marriage are 1) limited funds and human resources in overcoming child marriage, 2) there are community role models who are permissive towards child marriage, and 3) there is no collaboration between stakeholders in preventing underage child marriage. The recommendation for further research is that it is necessary to expand the research location, such as at the Central Java level so that it can produce a complex picture and formulate effective and integrative strategies.